Emotional and Psychological Impacts on Bullying Perpetrators - Waluyo Widodo; Sugiarto, Sugiarto; Kus Hendar; As'ari Latif; Mohamad Ardin Suwandi (Berkala Ilmiah Pendidikan, 2025)
This study aims to explore the emotional and psychological impacts experienced by bullying perpetrators and to analyze the influence of parenting styles on the development of such behavior within the context of Madrasah Aliyah (Islamic Senior High Schools). Using a qualitative case study approach, data were collected through in-depth interviews, observations, and documentation involving perpetrators, guidance and counseling (BK) teachers, and school staff. The findings indicate that bullying perpetrators often experience emotional distress, including feelings of guilt, remorse, and behavioral changes such as social withdrawal following disciplinary actions. Contributing factors to these behaviors include unsupportive parenting styles, poor family communication, and social environmental pressures. Notably, several perpetrators demonstrated a willingness to change after undergoing counseling and engaging in personal reflection. This study underscores the importance of a comprehensive rehabilitative approach that goes beyond punitive measures, emphasizing the need for ongoing emotional and psychological support to effectively address bullying behavior.